Analysis of Cyber-Attacks in IoT-based Critical Infrastructures - Das, Resul; Gündüz, Muhammed Zekeriya (My University, 2019)
Every country in the world has very important critical infrastructures that provide important services such as electroniccommunications, energy, banking and finance, critical public services, transportation and water management. Each countryhas different strategies for sector-based critical infrastructures. With the increase in IoT-based solutions, network and Internetconnections are established in these critical infrastructures. Therefore, these critical systems included in information networks arealso subject to digital attacks. It is of great importance to identify the possible types of cyber attacks, to take various precautionsagainst these attacks and to develop protection methods. Especially today, it is vital to protect these critical infrastructures fromcyber-attacks. This paper examines the attacks on critical infrastructures, especially in recent years, and presents the most commonattacks. Furthermore, security approaches to mitigate or prevent IP-based cyber-attacks are mentioned.
Keywords: Bilgisayar Bilimleri; Yazılım Mühendisliği